Natural fibro-granular composite as a novel sustainable sound-absorbing material. (October 2021) - Ehsan Samaei, Seyed; Berardi, Umberto; Taban, Ebrahim; Soltani, Parham; Mohammad Mousavi, Seyyed
Highlights: An innovative natural fibro-granular composite was developed for sound absorption. RSM-CCD approach was used to determine the optimum levels of independent variables. A quadratic model was proposed to identify effects of independent variables on SAA. The results pointed to the promising acoustic behavior of fibro-granular composites. JCA model can successfully capture the trend of experimental data. Abstract: An innovative natural fibro-granular composite made of kenaf fibers and waste rice husk granules is developed and presented in this paper. The optimization of the sound absorption coefficient (SAC) of the composites was investigated through the impedance tube method. The central composite design (CCD) technique with response surface methodology (RSM) was used to design the experiments. A quadratic model was established to identify the effects of independent variables, including the thickness (20–60 mm), density (100–300 kg/m 3 ), binder content (10–30 %w/w), and fiber to granule ratio (0.33–3) on the sound absorption average. The accuracy of the proposed model was assessed using ANOVA, and the results demonstrated that all the independent variables were significantly associated with sound absorption. The RSM-CCD model provided the combination for the optimized composite, i.e. thickness of 50 mm, density of 200 kg/m 3, binder content of 15 %w/w, and fiber to granule ratio of 2.33. The fibro-granular composite prepared using the optimized results was further characterized in terms of SAC, airflow resistivity, tortuosity, and viscous and thermal characteristic lengths. The results pointed to the promising acoustic behavior of the optimized fibro-granular material. Results show that at all frequencies, the optimized fibro-granular sample provides higher sound absorption compared with samples made of 100% kenaf or 100% rice husk. The frequency-dependent SAC of the optimized material was also predicted by the empirical Delany-Bazley model and the phenomenological model of Johnson-Champoux-Allard, although this last model showed superior prediction performance.